2017
DOI: 10.1177/0890334417741881
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Urban Versus Rural Residence on the Relationship Between Type of Birth Attendant and Early Initiation of Breastfeeding in Ghana

Abstract: Findings from the study highlight the need for focused, context-specific, early initiation of breastfeeding promotion and intervention, especially for women and their birth attendants in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Seven studies reported that institutional delivery was associated with higher odds of EIBF [ 19 , 22 , 24 , 32 , 34 , 35 , 37 ]. Other studies identified that deliveries by skilled birth attendants were positively associated with EIBF [ 14 , 15 , 17 , 18 , 21 , 38 ]. Haile et al [ 18 ] pointed out that the type of birth attendant played an important role in EIBF, particularly in rural areas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies reported that institutional delivery was associated with higher odds of EIBF [ 19 , 22 , 24 , 32 , 34 , 35 , 37 ]. Other studies identified that deliveries by skilled birth attendants were positively associated with EIBF [ 14 , 15 , 17 , 18 , 21 , 38 ]. Haile et al [ 18 ] pointed out that the type of birth attendant played an important role in EIBF, particularly in rural areas.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies identified that deliveries by skilled birth attendants were positively associated with EIBF [ 14 , 15 , 17 , 18 , 21 , 38 ]. Haile et al [ 18 ] pointed out that the type of birth attendant played an important role in EIBF, particularly in rural areas. EIBF practice was reported to also be associated with antenatal care (ANC) visits.…”
Section: Resultsmentioning
confidence: 99%
“…The Moderating effect of urban versus rural residence on the relationship between type of birth attendant and early initiation of breastfeeding in Ghana [22] concluded that the role of birth attendant is very important in the early initiation of breastfeeding, almost the same as the role of healthcare provider and the birth attendant in educating the mother for initiation of the breastfeeding of the first hour is directly related to the educational, moral and health literacy of the birth attendants and Bangladesh [23] the mothers having normal virginal delivery started breastfeeding within one hour as compared to women who were having C-section.…”
Section: Resultsmentioning
confidence: 99%
“…The current study utilizes data from the 2014 Ghana Demographic and Health Survey, a nationally representative cross-sectional survey that provides up-to-date estimates and a snapshot view of the current state of health of the Ghanaian population 14 . The GDHS is nationally and privately funded and includes a total of 3 questionnaires: household questionnaire, man's questionnaire and woman's questionnaire 15,16 .…”
Section: Datamentioning
confidence: 99%